2012
DOI: 10.1155/2012/159423
|View full text |Cite
|
Sign up to set email alerts
|

Flux Analysis of the Trypanosoma brucei Glycolysis Based on a Multiobjective-Criteria Bioinformatic Approach

Abstract: Trypanosoma brucei is a protozoan parasite of major of interest in discovering new genes for drug targets. This parasite alternates its life cycle between the mammal host(s) (bloodstream form) and the insect vector (procyclic form), with two divergent glucose metabolism amenable to in vitro culture. While the metabolic network of the bloodstream forms has been well characterized, the flux distribution between the different branches of the glucose metabolic network in the procyclic form has not been addressed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Thus, an increase of NADPH demand may lead to an increase of acetate production from glucose metabolism. The suggested role of MEc is consistent with a recent in silico analysis of flux distribution between the different metabolic branches using a multiobjective-criteria bioinformatics approach (59). The simulations predict that ME activity is primarily responsible for the high flexibility observed for the excreted succinate/acetate ratio (33,54).…”
Section: Discussionsupporting
confidence: 84%
“…Thus, an increase of NADPH demand may lead to an increase of acetate production from glucose metabolism. The suggested role of MEc is consistent with a recent in silico analysis of flux distribution between the different metabolic branches using a multiobjective-criteria bioinformatics approach (59). The simulations predict that ME activity is primarily responsible for the high flexibility observed for the excreted succinate/acetate ratio (33,54).…”
Section: Discussionsupporting
confidence: 84%
“…1A). In this context, the role of PPDK is probably to participate in the maintenance of the glycosomal ATP/ADP balance, as proposed before (6,7).…”
Section: Resultsmentioning
confidence: 76%
“…1A), however, this has not been experimentally investigated so far (7,49). To address this question, we generated a double ⌬ppdk/⌬pepck knock-out mutant by deleting the PEPCK gene in the PPDK null background (⌬ppdk).…”
Section: Resultsmentioning
confidence: 99%
“…data). A multiobjective-criteria bioinformatics analysis of the flux distribution of the procyclic glucose metabolism showed that this high flexibility is due to flux redistribution from the succinate branch to the acetate branch through the NADP + -dependent malic enzymes (steps 6a, 6b) (Ghozlane et al, 2012). The procyclic trypanosomes express two malic enzyme isoforms: the cytosolic malic enzyme (MEc) isoform, which is synergistically essential with the pentose phosphate pathway for NADPH production; and the essential mitochondrial malic enzyme (Mem) isoform (Leroux et al, 2011;Allmann et al, 2013).…”
Section: Connections Between the Acetate And Succinate Branches Provimentioning
confidence: 99%